2018
DOI: 10.1016/j.jaerosci.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of bioaerosol: A bridge and opportunity for many scientific research fields

Abstract: Bioaerosol collectively refers to all suspended particles of biological origins in the air. In theory, all biological materials can be released either directly or resuspension into the air upon various disturbances from the earth surfaces such as soils, oceans, animals, forests, humans and etc. Once airborne, as shown in Fig. 1 biaoerosol particles could undergo human inhalation, dry/wet depositions, aerial transport, ice nucleation, cloud condensation processes, atmospheric transformation and others. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…The presence of bioaerosols has been suspected to significantly impact human health as a biological pollutant (Douwes et al, 2003;Kim et al, 2018;Yao, 2018). Bioaerosols are not self-contained pollutants, but a mixture of various compounds, for example, bacteria, fungi, viruses, and pollen (Jiayu et al, 2019).…”
Section: Bioaerosol Componentsmentioning
confidence: 99%
“…The presence of bioaerosols has been suspected to significantly impact human health as a biological pollutant (Douwes et al, 2003;Kim et al, 2018;Yao, 2018). Bioaerosols are not self-contained pollutants, but a mixture of various compounds, for example, bacteria, fungi, viruses, and pollen (Jiayu et al, 2019).…”
Section: Bioaerosol Componentsmentioning
confidence: 99%
“…Instead, we focus on a high-level discussion of pressing scientific questions, grand challenges, sampling recommendations, and needs for cross-disciplinary collaboration. Comprehensive reviews can be found elsewhere (Yao 2018;Buters et al 2018;Delort and Amato 2017;N uñez et al 2016a, 2016b; Fr€ ohlich-Nowoisky et al 2016; Sofiev and Bergmann 2013;Despr es et al 2012;Xu et al 2011;Morris et al 2011;Womack, Bohannan, and Green 2010;Georgakopoulos et al 2009;Jones and Harrison 2004;Madelin 1994). Contributions were compiled from a group of authors with diverse sets of backgrounds and expertise, with more emphasis added from the perspective of the atmospheric sciences than others, e.g., health sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol (or airborne particulate matter, PM) is defined by the International Union of Pure and Applied Chemistry, IUPAC as: “ Mixtures of small particles (solid, liquid, or a mixed variety) and the carrier gas (usually air); owing to their size, these particles (usually less than 100 μ m and greater than 0.01 μ m in diameter) have a comparatively small settling velocity and hence exhibit some degree of stability in the earth’s gravitational field” (Calvert, 1990). Viruses are a category of aerosol of biological origin and referred to as bioaerosol (Douwes et al , 2008; Yao, 2018). Viruses, such as SARS, H1N1 and MERS-CoV, pose distinct health risks, in addition to the known aerosol health effects (Yao, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are a category of aerosol of biological origin and referred to as bioaerosol (Douwes et al , 2008; Yao, 2018). Viruses, such as SARS, H1N1 and MERS-CoV, pose distinct health risks, in addition to the known aerosol health effects (Yao, 2018). Their transmission from person to person through the atmosphere is a pathway of infection that is not well explored, although a very important one, especially for the indoor environments (Nazaroff, 2016; Yao, 2018; Anderson et al , 2020; Fears et al , 2020).…”
Section: Introductionmentioning
confidence: 99%